Attributing the streamflow variation by incorporating glacier mass balance and frozen ground into the Budyko framework in alpine rivers - Yang, Linshan; Feng, Qi; Ning, Tingting; Lu, Tiaoxue; Zhu, Meng; Yin, Xinwei; Wang, Jingru (Journal of hydrology (Amsterdam), 2024)
•Glacier mass balance and frozen ground were incorporated into the Budyko framework.•Modified Budyko framework could improve the streamflow simulation in alpine region.•Streamflow variation was clustered into 3 classes in 22 rivers of Qilian Mountains (QLM).•Glacier mass balance contributed to variation in streamflow by −2.42–11.63 % in QLM.•Frozen ground degradation contributed to decrease in streamflow by −31.09–−0.43 % in QLM. The remarkable climate change has profound impact on the alpine hydrology, it remains unclear to date on the role of the changes in glacier mass balance and frozen ground degradation to the regional streamflow variation. Here, we incorporated the glacier mass balance and frozen ground degradation into the Budyko framework and used the elasticity method to attribute the variation of annual streamflow for 22 rivers in Qilian Mountains (QLM) from 1982 to 2015. The results indicate the simulated annual streamflow that considering glacier mass balance and frozen ground can explain more than 90 % of observed streamflow at a significance of p < 0.01, especially for the rivers with high glacier coverage. The elasticity method revealed the simulated streamflow variation can explain more than 91 % of variation in respect to the detected streamflow variation. It indicates the robustness of the elasticity method and highlights the ability of capturing the variation in streamflow with the Budyko framework that incorporated glacier mass balance and frozen ground. The streamflow variations in the 22 rivers of QLM were clustered into 3 classes. The distribution of the contributions of precipitation to streamflow variation in the 3 classes was consistent to the streamflow variation. The precipitation played a dominant role in the rivers with increased streamflow, and ET0 played a dominant role in the rivers with decreased streamflow in QLM. The impact of vegetation on streamflow variation illustrated the strong regional divergence with the contribution varied between −34.55 % and 36.79 %. The contribution of glacier mass balance and frozen ground degradation to streamflow variation were moderate with negative contributions of frozen ground degradation to the streamflow variation varying between −31.09 % and −0.43 %, while the contribution of glacier mass balance to variation in streamflow varied between −2.42 % and 11.63 % in QLM. The results could be help to understand the alpine hydrological processes under the background of climate warming and utilized for sustainable water resource management in inland region.